Membrana celulares modelo: uma revisão teórica - Paixão, Rafaela Ribeiro (Universidade Federal de São Carlos, 2024)
Knowledge about the cell membrane is extremely important as it is what divides the boundaries of the cell, separating the extracellular environment from the intracellular environment, and is responsible for the transport of substances and is the target of study for the development of techniques and mechanisms in various areas of Science, including drug delivery systems, selective sensors, etc. Due to factors such as cellular diversity, dynamic structure and complex metabolism, they make the study of the membrane difficult, making it necessary to seek alternatives to better understand this system. In this context, Model Cell Membranes emerge, which are membrane models created to mimic the structure and composition present in cell membranes. Model membranes can be mimicked in different structures and with numerous compositions, which allows applications with different purposes and with different techniques for study and characterization, including new materials, nanoscale encapsulation technology for foods and medicines, biological sensors, etc. Biophysical and biochemical interaction studies with model membranes are a simple and effective approach to knowing and understanding the dynamics of natural cell membranes.
Model cell membranes: a theoretical review
Keywords: Membranas; Lipídios; Langmuir; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA